The effects of a weighted vest on aggressive and self-injurious behavior in a child with autism. (June 2013) - Davis, Tonya N.; Dacus, Sharon; Strickland, Erica; Copeland, Daelynn; Chan, Jeffrey Michael; Blenden, Kara; Scalzo, Rachel; Osborn, Staci; Wells, Kellsye; Christian, Krisann
<x xml:space="preserve">Abstract</x> Objective: Analyse the effects of a weighted vest on the aggressive and self-injurious behavior of a young boy with autism. Methods: The effects of the weighted vest were examined during a functional analysis utilizing an ABAB design with an embedded multielement design, in which the participant wore a five pound weighted vest or no vest. Results: The results do not suggest the existence of a functional relationship between the use of a weighted vest and challenging behavior, as the weighted vest had no marked effect on levels of aggression and self-injurious behavior. Conclusions: Weighted vests are a commonly implemented form of sensory integration therapy, frequently used as a treatment for disruptive behaviors associated with autism spectrum disorder [Stephenson J, Carter M. The use of weighted vests with children with autism spectrum disorders and other disabilities. Journal of Autism and Developmental Disabilities 2009;39:105–114]. However, the current findings support previous literature which states that the use of weighted vests does not appear to decrease challenging behavior.